PENINGKATAN KUANTITAS DAN KUALITAS PRODUKMELALUI PERBAIKAN TEKNOLOGI PROSES PRODUKSIPADA USAHA KERAJINAN BATU PUTIH GUNUNGKIDUL - Ismanto, Yuni Pratiwi dan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Gunungkidul area, especially Semin and Semanu District, is a whitestone production. This area is a central of stone craft for export anddomestic market.The barriers are the limitation of production tools, low quality ofcraft product, and traditional management. They caused the development ofstone craft are slow. Despite, these conditions make consumer's complaint,domestic and also consumer's foreign.The 1st year IbPE team from Janabadra University gave problemsolving by creating the moulding machine for UD. Dwi Karya Sejahtera(Small and Medium Enterprise 1) and Frais machine for UD. Mustika Alam(Small and Medium Enterprise 2). The team also gives management trainingfor SMEs.SME's can decrease the broken of raw materials, which are onprocessing from 35% to 5% by using the moulding machine. The SME'sproductivities can increase by using Frais machine, from 102 m2 per monthto 729 m2 craft stone per month. Management training also increases theskill management for entrepreneur of craft stone, from traditional to modernSME's.